Zanik debaty? Odmienność systemów: media – Kościół – nauka - Doda-Wyszyńska, Agnieszka (Człowiek i Społeczeństwo, 2022)
The main question that the article poses is whether today there is still a possibility of media debate, for example on religion or the Church; or perhaps the system of mass media is governed by the logic of what Niklas Luhmann calls the thematic career. Mass media discuss various topics, but probably do not help to search for solutions for intra- and intersystem conflicts. According to Luhmann, mass media, politics, science and religion are autopoietic systems; they develop by their own rules. They are sensitive to external conditions, but primarily refer to what they have developed within themselves. Drawing upon Niklas Luhmann’s systems theory and using the analysis of the old debate (around Galileo), still without participation of mass media, and the current debate from 2012 when Richard Dawkins met Cardinal George Pell, I ask a question about its current shape. This is presented against the backdrop of the problem of how much the so-called synodality of the Catholic Church helps a given religion influence other social systems (such as science) and generally – social life. Why is it so difficult to fulfil the conditions of debate in the context of the three systems: religion (based on the example of the Catholic religion), media (mainly the Internet) and science? Perhaps it is because we deal with extremely different social systems which are mostly concerned with their own internal development. Moreover, the situation of reflection on the phe- nomenon of religion and social systems always becomes complicated by a specific global situation, both in the Church (e.g. synodality), and outside it (e.g. pandemic, war, new social movements).